Structure and spectra of photochemically obtained nanosized silver particles in presence of modified porous silica - Galina Krylova; Anna Eremenko; Natalia Smirnova; Susie Eustis (International Journal of Photoenergy)
Mesoporous silica powders and films modified with organic sensitizer benzophenone were used as photocatalysts in the reaction of silver ion reduction by isopropyl alcohol under UV-irradiation with λ= 253.7 nm and 365 nm in presence of colloidal silica as stabilizer. Morphological changes of silver colloids during irradiation were studied using transmission electron microscopy, and correlated to the absorption spectra.